2018
DOI: 10.7717/peerj.4538
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological evidence for temporal dynamics associated with attentional processing in the zoom lens paradigm

Abstract: BackgroundVisuospatial processing requires wide distribution or narrow focusing of attention to certain regions in space. This mechanism is described by the zoom lens model and predicts an inverse correlation between the efficiency of processing and the size of the attentional scope. Little is known, however, about the exact timing of the effects of attentional scaling on visual searching and whether or not additional processing phases are involved in this process.MethodElectroencephalographic recordings were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
(71 reference statements)
0
4
0
Order By: Relevance
“…When the homogenous distractor was delivered in between the target and the singleton distractor (non-contiguous trials), participants may have broadened their attentional focus attending all the ipsilateral stimuli in order to identify the target frequency and select its location. Evidence from visual search studies has indicated that the amplitude of the N2pc can reflect the size of the attentional focus, with larger N2pc amplitudes when participants were explicitly instructed to broaden their attentional focus to cover a larger portion of visual space (Zhang, Liang, Zhang, Fu & Wu, 2018). Furthermore, increasing the number of task-relevant targets within a visual search array resulted in increased N2pc amplitudes (Pagano & Mazza, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…When the homogenous distractor was delivered in between the target and the singleton distractor (non-contiguous trials), participants may have broadened their attentional focus attending all the ipsilateral stimuli in order to identify the target frequency and select its location. Evidence from visual search studies has indicated that the amplitude of the N2pc can reflect the size of the attentional focus, with larger N2pc amplitudes when participants were explicitly instructed to broaden their attentional focus to cover a larger portion of visual space (Zhang, Liang, Zhang, Fu & Wu, 2018). Furthermore, increasing the number of task-relevant targets within a visual search array resulted in increased N2pc amplitudes (Pagano & Mazza, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Alongside MVPA analysis, with the aim to explore potential differences in the observed effects between univariate (i.e., ERPs) and MVPA techniques of EEG data, we performed univariate ERPs analyses both in cue-and target-locked time windows. Cue-and target-locked ERPs components were identified based on previous literature that investigated the neuroelectric correlates of attentional zooming mechanisms in the TD population (Luo et al, 2001;Fu et al, 2005;Song et al, 2006;Zhang et al, 2018), through visual inspection of the ERPs waveform and topographical scalp maps. Following previous studies, to investigate the modulation of early visual evoked potentials by the scale effect of the spatial attention, P1 and N1 components were calculated, choosing, respectively, time windows of 100-150 ms and 200-250 ms after cue onset (cue-locked analysis; large vs. small cue) and time windows of 140-190 ms and 220-270 ms after target onset (target-locked analysis; target location following large vs. small cue trials).…”
Section: Univariate Erps Analysismentioning
confidence: 99%
“…Following previous studies, to investigate the modulation of early visual evoked potentials by the scale effect of the spatial attention, P1 and N1 components were calculated, choosing, respectively, time windows of 100-150 ms and 200-250 ms after cue onset (cue-locked analysis; large vs. small cue) and time windows of 140-190 ms and 220-270 ms after target onset (target-locked analysis; target location following large vs. small cue trials). These analyses were computed on the central posterior ROI (for a graphical representation, see Supplementary Figure 2), which was the most representative clusters of electrodes to investigate ERPs components associated to cue-size modulation, based on previous literature (Luo et al, 2001;Fu et al, 2005;Song et al, 2006;Zhang et al, 2018) and to visual inspection of topographical scalp maps. Regarding cue-locked analysis, we performed separated repeated measures ANOVA on the peak latency and mean amplitude, separately, of P1 and N1 components with the aim of testing whether ERPs modulations are influenced by the Cue-Size (within-subjects factor: large and small), using as between-subjects factor the Group (ASD and TD).…”
Section: Univariate Erps Analysismentioning
confidence: 99%
“…As one of the most important cognitive functions of humans, visuospatial selective attention can focus attention on a certain spatial area and allocate attentional resources rationally during the perception of the visual target. The “spotlight theory” of attention also suggests that attention, like a spotlight, can be “focused” on a region of visual space at any given moment, and only stimuli in this area can be effectively perceptually analyzed [ 1 , 2 ]. However, most stroke patients have spatial attention disorder, so their spatial attention distribution and spatial attention fineness will be affected.…”
Section: Introductionmentioning
confidence: 99%